2020
DOI: 10.1111/codi.15483
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal versus vertical plication of the rectovaginal septum in transperineal repair of anterior rectocele: a pilot randomized clinical trial

Abstract: Aim: Anterior rectocele is usually an asymptomatic condition in many women, yet it can be associated with obstructed defaecation syndrome (ODS). Transperineal repair of rectocele (TPR) has been followed by variable rates of improvement in ODS. The present pilot randomized clinical trial aimed to evaluate the outcome of TPR with vertical plication (VP) of the rectovaginal septum compared to horizontal plication (HP).Methods: Adult women with anterior rectocele were recruited to the study and were randomly alloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 22 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…Omission of levatorplasty only ( n = 71): The omission of levatorplasty resulted in postoperative improvement in ODS symptoms in 66.7%-78.2% of patients[ 27 , 37 , 38 - 40 ]. The reduction in ODS scores ranged between 32.8% and 53.0%[ 27 , 37 , 40 ]. A significant reduction in rectocele size was recorded in 45.8%-76.3% of patients[ 27 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Omission of levatorplasty only ( n = 71): The omission of levatorplasty resulted in postoperative improvement in ODS symptoms in 66.7%-78.2% of patients[ 27 , 37 , 38 - 40 ]. The reduction in ODS scores ranged between 32.8% and 53.0%[ 27 , 37 , 40 ]. A significant reduction in rectocele size was recorded in 45.8%-76.3% of patients[ 27 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in ODS scores ranged between 32.8% and 53.0%[ 27 , 37 , 40 ]. A significant reduction in rectocele size was recorded in 45.8%-76.3% of patients[ 27 , 37 ]. Youssef et al [ 40 ] reported an increase in MRP, in contradiction to another study that reported a decrease in anal pressures[ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations